2020
DOI: 10.1186/s13229-020-00367-w
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the phenotypic heterogeneity in sensory features in autism spectrum disorder: a factor mixture modelling approach

Abstract: Background: Heterogeneity in the phenotypic presentation of autism spectrum disorder (ASD) is apparent in the profile and the severity of sensory features. Here, we applied factor mixture modelling (FMM) to test a multidimensional factor model of sensory processing in ASD. We aimed to identify homogeneous sensory subgroups in ASD that differ intrinsically in their severity along continuous factor scores. We also investigated sensory subgroups in relation to clinical variables: sex, age, IQ, social-communicatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 79 publications
1
33
1
Order By: Relevance
“…A non-linear relationship was observed with sensory seeking more pronounced in 6-9 year-olds but diminishing in older age groups. Other studies, however, have reported no age-related differences in sensory processing (Dwyer et al, 2020;Simpson et al, 2019;Tillmann et al, 2020). Sex-related differences in sensory processing are also inconsistently reported across the research.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…A non-linear relationship was observed with sensory seeking more pronounced in 6-9 year-olds but diminishing in older age groups. Other studies, however, have reported no age-related differences in sensory processing (Dwyer et al, 2020;Simpson et al, 2019;Tillmann et al, 2020). Sex-related differences in sensory processing are also inconsistently reported across the research.…”
Section: Introductionmentioning
confidence: 84%
“…Synonyms for sensory hyper-reactivity include sensory sensitivity, sensory avoiding, withdrawal and sensory defensiveness, and for hypo-reactivity include poor registration of sensory inputs, sensory inattention, and attenuated responses to sensory stimuli. Autistic children and adults who demonstrate typical or only mild sensory modulation symptoms have been observed to experience better adaptive functioning (Ausderau et al, 2016;Tillmann et al, 2020). For example, hyper-reactive behaviors such as avoiding have been associated with decreased activity participation and can make daily living tasks more challenging (Little et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we also reported a signi cant interaction between dSSP score and chronological age of the subjects. This association may be driven by the load of comorbidity reported in the individuals with ASD, since previous studies reported higher levels of sensory reactivity in those severity of associated comorbidities (Kreiser & White, 2015, Tillmann et al, 2020. This association was observed in subjects with comorbid anxiety or depressive symptoms (MacLennan et al, 2021;Rossow et al, 2021) but also somatic complaints (Lefter et al, 2020).…”
Section: Discussionmentioning
confidence: 87%
“…Importantly, in previous studies, heterogeneity in the autistic population has been recognized as a reason explaining inconsistent findings. Person-centered approaches that aim to characterize heterogeneity in a population by identifying homogeneous subgroups of similar individuals (Nylund-Gibson & Choi, 2018) are becoming increasingly utilized in autism research and have demonstrated promise when applied across different aspects of the autistic phenotype including social functioning (Uljarevi c et al, 2020), sensory features (Tillmann et al, 2020;Uljarevi c, Lane, et al, 2016), and RRBIs (Zheng et al, 2019). However, no study to date has applied this approach to anxiety.…”
Section: Introductionmentioning
confidence: 99%